2022
DOI: 10.1002/adfm.202211304
|View full text |Cite
|
Sign up to set email alerts
|

Anion‐Modulated Chemical Doping of Organic Hole Conductor Boosts Efficiency and Stability of Perovskite Solar Cells

Abstract: Chemical doping of organic semiconductors enables significant progress in improving their optoelectronic performance. However, the correlation between doping counter ions and charge-transport mechanism has not been yet well-understood. In this study, it is discovered that the anion-dependent degree of delocalization (DOD) of lithium-based dopants significantly determines the doping kinetics as well as the conductivity of organic hole transport layer (HTL), leading to large variation in solar cell efficiency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…5h). [44][45][46] Then, the operational stability tests of the devices prepared using CB and HAc have been performed under maximum power point tracking (MPPT) conditions (Fig. S15, ESI †).…”
Section: Papermentioning
confidence: 99%
“…5h). [44][45][46] Then, the operational stability tests of the devices prepared using CB and HAc have been performed under maximum power point tracking (MPPT) conditions (Fig. S15, ESI †).…”
Section: Papermentioning
confidence: 99%
“…Recently, the Zhang group reported the anion modulated chemical doping process of Spiro-OMeTAD also influences the LSE of devices. 98 Specifically, the degree of delocalization (DOD) of the counterions (PF 6 , TFSI, and PFSI) in lithium salts determines the cation exchange between Li + and Spiro-OMeTAD + , which influences the strength and reversibility of LSE. For example, PF 6 with a low DOD resulted in a strong and reversible LSE.…”
Section: Charge Carrier Accumulationmentioning
confidence: 99%
“…The results showed that the increase of the diffusion length was related to the photogeneration of carriers, but not to the absolute density of carriers. Recently, the Zhang group reported the anion modulated chemical doping process of Spiro-OMeTAD also influences the LSE of devices . Specifically, the degree of delocalization (DOD) of the counterions (PF 6 , TFSI, and PFSI) in lithium salts determines the cation exchange between Li + and Spiro-OMeTAD + , which influences the strength and reversibility of LSE.…”
Section: Physical Mechanisms Of Lsementioning
confidence: 99%
“…[22,23] The involved ionic dopant, bis(trifluoromethane)sulfonimide lithium salt (LiTFSI, Figure 1A), often instigates moisture absorption and ion migration, which induces compositional variation and leads to the degradation of HTLs. [18,24] Moreover, the escape of volatile species such as 4-tert-butylpyridine (tBP) from the film under heat results in severe phase segregation in the HTLs which is often caused by lithium-salt aggregation. [21,25] Long post-oxidation process is typically required due to the low efficiency of the airactivated chemical doping process of Spiro-OMeTAD, leading to low productivity and reliability of the HTL fabrication.…”
Section: Introductionmentioning
confidence: 99%